Perbandingan Volume Kendaraan Antara Pagi Hari dan Siang Hari di Jalan Panjaitan - Ferdian, Adnan (Unmuh Babel Press, 2025)
This study aims to evaluate the comparison of vehicle numbers between morning and afternoon on Jalan Panjaitan, which is one of the roads with high traffic activity. The data used comes from secondary records of vehicle numbers during two periods, namely morning and afternoon. This study was conducted to observe differences in traffic density levels during these two periods. The results of the study show a significant difference in the number of vehicles between morning and afternoon, with the morning period tending to have more vehicles than the afternoon period. These findings can be used as a basis for decision making related to traffic management, traffic light timing adjustments, and transportation planning in the are.